Religious moderation education based on local wisdom values for the young generation in southeast aceh - Paulinus Tibo; Paulus Halek Bere (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The religious moderation education movement serves as a teaching model aimed at helping the younger generation enhance their understanding and quality of perspectives, attitudes, and life practices rooted in local culture as religious teachings, enabling them to discuss these within the diverse contexts and civilizations of real community life, particularly in Southeast Aceh. The research method used is a phenomenological qualitative study and literature review with descriptive analysis techniques. Research findings: The younger generation does not fully understand the importance of applying the values of religious moderation in a pluralistic and multicultural society and religious context. Young people have not sufficiently understood the values of religious moderation within the context of their respective religious teachings, despite their commitment to applying them in school, their families, and society. We recommend that young people, particularly in Southeast Aceh, receive contextual education on religious moderation.